2018
DOI: 10.1111/mcn.12604
|View full text |Cite
|
Sign up to set email alerts
|

Livestock ownership is associated with higher odds of anaemia among preschool‐aged children, but not women of reproductive age in Ghana

Abstract: Livestock ownership may influence anaemia through complex and possibly contradictory mechanisms. In this study, we aimed to determine the association of household livestock ownership with anaemia among women aged 15–49 years and children aged 6–59 months in Ghana and to examine the contribution of animal source foods (ASFs) to consumption patterns as a potential mechanism mediating this association. We analysed data on 4,441 women and 2,735 children from the 2014 Ghana Demographic and Health Survey and 16,772 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 79 publications
5
20
2
Order By: Relevance
“…Ahenkorah et al ( 38 ) observed that the odds of anemia were twice as high among Ghanaian pregnant women exposed to domestic livestock compared to those not exposed. In contrast, Jones et al ( 46 ) found no association between livestock ownership and anemia among non-pregnant Ghanaian women in models adjusting for sociodemographic characteristics of women, access to improved water and sanitation, and malaria prevention strategies. Jones et al ( 46 ) also analyzed the association of ownership of specific livestock species with anemia among women and found no associations.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Ahenkorah et al ( 38 ) observed that the odds of anemia were twice as high among Ghanaian pregnant women exposed to domestic livestock compared to those not exposed. In contrast, Jones et al ( 46 ) found no association between livestock ownership and anemia among non-pregnant Ghanaian women in models adjusting for sociodemographic characteristics of women, access to improved water and sanitation, and malaria prevention strategies. Jones et al ( 46 ) also analyzed the association of ownership of specific livestock species with anemia among women and found no associations.…”
Section: Resultsmentioning
confidence: 93%
“…In contrast, Jones et al ( 46 ) found no association between livestock ownership and anemia among non-pregnant Ghanaian women in models adjusting for sociodemographic characteristics of women, access to improved water and sanitation, and malaria prevention strategies. Jones et al ( 46 ) also analyzed the association of ownership of specific livestock species with anemia among women and found no associations. Conversely, Flores-Martinez et al ( 42 ) found better anemia outcomes among women who lived in sheep- and goat-owning households in Afghanistan, but worse outcomes with chicken ownership, adjusting for household and maternal characteristics, pregnancy status, water source, and region.…”
Section: Resultsmentioning
confidence: 93%
“…Ownership of any livestock and the number of free-range poultry, corral chickens, sheep, goats, and pigs owned by households served as the primary independent variables. Guided by existing evidence on factors that influence the anaemia status of children, we controlled for selected sociodemographic characteristics [9, 21, 22]. Using a food frequency questionnaire, caregivers were asked about children’s dietary intake in the week prior to the interview.…”
Section: Methodsmentioning
confidence: 99%
“…Such enhanced food security is linked with improved intake of micronutrients, including iron, which is essential for preventing iron deficiency anaemia [8]. Ironically, the presence of household animals may also increase the likelihood of certain infections that elevate anaemia risk, particularly among young children [9]. The potential linkages among household livestock ownership, household food security, and anaemia in children are complex and potentially contradictory.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation